2016
DOI: 10.1016/j.eurpsy.2016.01.249
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity between delusional disorder and sensory deficits. Results from the deliranda case register

Abstract: IntroductionSensory deficits such as blindness and deafness are very common forms of disability, affecting over 300 million people worldwide according to World Health Organization estimates. These conditions can lead to misinterpretations of the environment, which may contribute to the development of a delusional disorder in predisposed people.ObjectivesThe objective of this study is to establish the prevalence of blindness and hearing loss across delusional disorder.AimsThe aim is to provide useful informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, the included studies dated before the standardisation of DD diagnostic criteria, and therefore lacked appreciation for the different manifestations of the disorder. Other studies suggest a comparable co-morbidity rate with affective disorders and suicidal behaviour between DD and SZ [12,13], though DD demonstrate a greater susceptibility to physical conditions [14] than in SZ [15].…”
Section: Comparisons Between Dd and Sz Cohortsmentioning
confidence: 92%
“…However, the included studies dated before the standardisation of DD diagnostic criteria, and therefore lacked appreciation for the different manifestations of the disorder. Other studies suggest a comparable co-morbidity rate with affective disorders and suicidal behaviour between DD and SZ [12,13], though DD demonstrate a greater susceptibility to physical conditions [14] than in SZ [15].…”
Section: Comparisons Between Dd and Sz Cohortsmentioning
confidence: 92%
“…28 More recent studies have also investigated the prevalence of vision and hearing loss in DD. 29 In a sample of 1,452 patients fulfilling DSM-5 DD criteria, 7.4% were found to have sensory deficits: vision loss (3.5%) and hearing loss (3.9%). These findings were in line with previous reports from de Portugal et al who found a 5.7% prevalence of sensory deficits in DD.…”
Section: Primary and Secondary Preventive Strategies At The Community...mentioning
confidence: 99%
“…34,36 Health screening Screening programs for sensory impairment and provision of treatment. 29 Suicide prevention Distress phone lines and public health announcements. 3 They found that men had a significantly higher frequency of premorbid substance use than women (30.3% vs. 11.3%).…”
Section: Community Levelmentioning
confidence: 99%
“…In DD populations, Porras-Segovia and colleagues [ 30 ] investigated the prevalence of blindness and hearing loss as part of an Andalusian DD case-register study (DelirAnda). The total sample of 1452 patients, all fulfilling DSM-5 criteria for DD, showed a 7.4% prevalence of sensory deficits: blindness (3.5%) and hearing loss (3.9%).…”
Section: Collaboration With Ophthalmology and Otolaryngologymentioning
confidence: 99%